Sistem Pendukung Keputusan Penentuan Team Leader Menggunakan Metode MOOSRA - Kristianto Hondro, Rivalri; Aripin, Soeb (Universitas Harapan Medan, 2022)
The best employees are employees who have their own quality, performance and excellence in their fields, while the best employees will later become team leaders for other employees. Each team leader is an example and role model by other employees, the selection of a team leader is done to give rewards to employees who have been serious about their company and this will be a motivation for other employees to be able to achieve company goals together, the process of selecting a team leader that is This is done by many companies, the selection is often carried out by appointing employees randomly and based on personal proximity, this makes many other employees experience injustice in a job and this can have a negative impact on the sustainability of the company. Because choosing the wrong person to be a team leader needs to be done the selection and selection of employees to become a team leader uses a system to avoid mistakes in selecting a team leader, a system can find accurate and precise value results based on the logic of a decision-making method. The MOOSRA method, which is a very complex method and has simple stages, is used in consideration of the selection of a team leader so that the results of the research from the calculation of the criteria value are found, a value of 0.585 is found which is the highest value as the first rank that deserves to be chosen as a team leader